+0  
 
0
28
1
avatar+288 

2y(3x + y - 2z) + 3x(y - 2x + z)

for x = -2, y = 2, and z = 1

 
 Jan 10, 2019
 #1
avatar+94526 
+1

2y(3x + y - 2z) + 3x(y - 2x + z)

for x = -2, y = 2, and z = 1

 

 

OK.....let's fill in what we know....

 

2(2) [  3(-2) + 2 - 2(1) ] + 3(-2) [ 2 - 2(-2) + 1 ]  =

 

4 [  - 6  + 2 - 2 ]  +   (-6) [2 + 4 + 1 ]    = 

 

4 [ -6 ]  +   (-6) [ 7 ]    =

 

-24    -   42   =

 

-66

 

 

cool cool cool

 
 Jan 10, 2019

25 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.